Evaluating the pectoralis nerve blocks I & II for mastectomy patients at an academic hospital: A prospective observational cohort study. - Pablo Samuel Tshiteta; Lunganga Toms Lushiku; Mathabe Sehlapelo (Student's Journal of Health Research Africa, 2026)
Background: Poorly managed perioperative mastectomy pain increases the incidence of chronic pain. The aim of this study was to compare PEC I & II blocks versus the administration of local anaesthesia (LA) via a surgical drain in female patients presenting for unilateral mastectomy. These techniques were compared with regard to postoperative pain scores, satisfaction, time to first request for systemic opioids postoperatively, opioid consumption, the incidence of postoperative nausea and vomiting (PONV), and complications. Methods: A prospective, cohort, observational, single-centre study with 33 female participants who were recruited via purposive sampling; three were excluded from the study. Participants were assigned to PEC blocks (Group P, n=15) or LA via surgical drain (Group S, n=15). Group S received the standard of care, which was administration of 2mg/kg of 0.5% bupivacaine with adrenaline (1:200,000) via the surgical drain. Group P received 0.2ml/kg of 0.5% bupivacaine plus adrenaline (1:200,000) in each fascial plane. Results: There were no significant differences in participants’ characteristics in the groups. The study showed no statistically significant difference between the pain scores of the groups at 30 minutes, 3, 6, and 24 hours postoperatively (p=0.660, p=0.160, p=0.894, p=0.931). The differences in patient satisfaction scores and morphine consumption were statistically insignificant. No complications were noted in either of the groups. No statistically significant relationship with the occurrence of vomiting and nausea and the specific technique. Conclusion: This study showed no difference between PEC I & II blocks and the administration of LA via a surgical drain in the management of postoperative pain in mastectomy patients. The techniques can be considered safe, as there was a low incidence of the described complications, including the incidence of PONV. Recommendations: The author recommends further research in the form of randomised controlled trials with larger sample sizes comparing all breast regional modalities.